Aging, Trade, and Migration - Chisik, Richard (World Bank, Washington, DC, 2016)
This study considers the role of demand-driven changes arising from population aging and how they affect the pattern of international trade as well as trade and immigration policy. An aging society can see a welfare-reducing reduction in its share of manufacturing output and this reduction is magnified by a decrease in trade costs (an increase in globalization). Immigration can ameliorate this outcome if it is directed toward younger immigrants. A unilateral tariff increase can also reduce firm delocation from an aging country, however, a reciprocated tariff increase will unambiguously harm the country with the older average population.